CHEMICAL COMPOSITION, HEALING PROPERTIES OF GARLIC AND ITS PEEL (Scientific journal of the Fergana State University, 2023)
The article determined the chemical composition of garlic fruits and peel using a special mass spectrometric method, which is used to determine macro- and microelements in food products. The procedure for analyzing the results of experiments in mg of a substance and its solubility in the same amount is given. Of these elements, vital, conditionally important and close to toxicity are shown. From the results it can be concluded, the amount of macro and micronutrients in the peel that we throw away as waste is different from the content of the fruit powder.